2000
DOI: 10.4319/lo.2000.45.2.0300
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon fluxes, degradation, and accumulation in an anoxic basin: Sediment trap results from the Cariaco Basin

Abstract: Organic carbon fluxes were measured in the anoxic water column of the Cariaco Basin under varying levels of primary productivity. Our results indicate that water column degradation of fresh organic matter in this anoxic setting is similar to what has been previously observed in the open ocean. Additionally, the rate at which carbon is consumed increases as primary productivity increases. These findings support the hypothesis that sulfate reduction is as efficient as aerobic respiration in degrading labile orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 49 publications
8
101
0
4
Order By: Relevance
“…Sinking organic matter in Cariaco Basin is primarily the product of phytoplankton productivity in the surface ocean (Thunell et al, 2000) and contains biosulfur predominantly as cysteine and methionine. The ratio of sulfur to carbon in fresh planktonic biomass is commonly estimated at 1.6% (Wollast et al, 1993) but was also found to range between 0.4% and 1.1% in a variety of diatoms, dinoflagellates, cyanobacteria, algae, and humic acids (Francois et al, 1987 and refs therein).…”
Section: Proto-kerogen Sulfur In Sinking Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinking organic matter in Cariaco Basin is primarily the product of phytoplankton productivity in the surface ocean (Thunell et al, 2000) and contains biosulfur predominantly as cysteine and methionine. The ratio of sulfur to carbon in fresh planktonic biomass is commonly estimated at 1.6% (Wollast et al, 1993) but was also found to range between 0.4% and 1.1% in a variety of diatoms, dinoflagellates, cyanobacteria, algae, and humic acids (Francois et al, 1987 and refs therein).…”
Section: Proto-kerogen Sulfur In Sinking Particlesmentioning
confidence: 99%
“…In this study, we approach these questions by interrogating the distribution of sulfur and its isotopic composition in sediment trap material from Cariaco Basin in the context of hydrographic profiles and particle composition time-series data (Thunell et al, 2000; http://imars.marine.usf.edu/CAR/). These µg-scale analyses are made possible via the novel use of multicollector inductively-coupled-plasma mass spectrometry to analyze bulk organic fractions (Raven et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, in 1998, a rate of < 300 gC m 2 y 1 was estimated. The vertical flux of organic carbon measured with the sediment traps follows a regular pat tern; minima occur between September and January and maxima between February and May (Figure 4).The magnitude of the flux tends to decrease with increasing water depth, and similar temporal variability is observed at all four depths (Figure 4).The material reaching the bottom of Cariaco is rich in opal, carbon ate, and organic carbon, and lithogenic materi al accounts for -50% of the total annual particulate flux [Thunell et al, 2000]. trap sample in early July 1997.This flux was associated with a turbidite generated by an earthquake that occurred along the Venezuelan coast.This event was described by Thunell et al [1999].…”
Section: Seasonal Hydrography Productivity and Settling Particulatementioning
confidence: 85%
“…This model prescribes the vertical profile of organic carbon flux as an exponential decay function based on surface production and depth. Since this model was developed from observations from an open, oxygenated Pacific Ocean environment, our results suggest that organic matter degradation in the anoxic Cari aco Basin is as efficient as that occurring in well-oxygenated waters [Thunell et a/.,2000].…”
Section: Implications For Estimates Of Fluxmentioning
confidence: 99%
See 1 more Smart Citation